INFEKSI JAMUR PADA GERIATRI - yossa tamia marisa; Roza Mulyana (Universitas Fort De Kock, 2020)
Elderly patients need special and thorough attention, because in elderly patients often occur more than one disease multipatologi. One of them is an infectious disease that is prone to occur in elderly patients due to decreased functional body reserve, decreased immunity, repeated hospital stays, diagnosis and therapy that is often late, decreased response to antibiotic therapy, and increased potential for side effects and interactions between drug. Fungal infections are an increasing problem in the elderly population including opportunistic fungal infections in elderly patients with immunocompromised conditions with multipatolgi disease and coincidence, post chemotherapy in malignancies, post-transplantation, or receive immunosuppressant therapy due to dermatological and rheumatological diseases.